Teacher well-being & engagement: The importance of teachers' interpersonal relationships quality at school - Purwaniningtyas, Dyah Ayu; Adira, Nesya; Kusmaryani, Rosita Endang; Nurhayati, Siti Rohmah (Faculty of Psychology, Universitas Negeri Yogyakarta, 2023)
Relationships are a fundamental feature of human life, making the study of relationships a crucial point in psychology, including within the context of schools. In addition to being a place of learning for students, schools serve as a workplace where teachers establish and maintain relationships. However, the majority of research conducted in schools still focuses only on student-student and teacher-student relationships. Moreover, there is limited specific research examining the importance of the quality of interpersonal relationships among teachers. This quantitative survey study aims to investigate the role of teacher-student interpersonal relationship quality as a predictor of Well-Being within the PERMA framework, encompassing Positive Emotion, Work Engagement, Meaning in Life, and Innovative Work Behavior among teachers in schools. Data were collected through offline and online surveys involving 455 teachers in public schools in Yogyakarta. Data analysis was conducted using Structural Equation Modeling (SEM) to test the model of interpersonal relationships among fellow teachers. The model testing indicated a good fit with the indices: Ï‡2(35, N=455) = 132; p<0.001; CFI = 0.977; SRMR = 0.041; RMSEA = 0.073, meeting the criteria set by Hair, Black, Babin, & Anderson (2019). Furthermore, overall, the quality of teacher-student interpersonal relationships significantly predicted the elements of psychological well-being, including affect (Î² = 0.631; p < 0.001), meaning in life (Î² = 0.549, p < 0.001), work engagement (Î² = 0.489; p < 0.001), and innovative work behavior among teachers in schools (Î² = 0.354; p < 0.001).